The Prevalence and Antimicrobial Susceptibility of Aeromonas Hydrophila Infection of Marketed Catfish in Besut, Terengganu - Nabilah Binti Meor Aziz, Fatin; Afiza Badaluddin, Noor; Binti Ismail, Norshida (International Journal of Engineering and Technology, 2018)
The commercial catfish covers about 37% of value of production in aquaculture sectors in Malaysia. Aeromonas hydrophila is the most common bacterial infection that occurred in catfish culture, mainly due to poor environment and water quality. The occurrence of bacterial disease affect the economical production of farm and may contribute to the excessive usage of antibiotics which can lead to antibiotic resistance problem. This recent study aimed to investigate the prevalence and antimicrobial susceptibility of A. hydrophila infection in commercial hybrid catfish, (Clarias gariepinus Ã— C. batracus) from several wet markets in Besut, Terengganu, Malaysia. A total of 28 catfish were collected randomly from different wet markets in Besut area. The organs such as heart, liver and spleen were taken out and inoculated on Blood Agar with ampicillin. The suspected colonies were subculture for at least three times to get pure colonies. For the identification of A.hydrophilla, the pure colonies were analysed using Gramâ€™s staining technique and five biochemical tests namely; Catalase, Oxidase, Methyl Red, Voges Proskauer and Triple Sugar Iron Test. For antimicrobial susceptibility test, the disc diffusion method was conducted by using four types of antibiotic discs, vancomycin, cephazolin, meropenem and colistin sulphate. The prevalence of A. hydrophila infection in this study were 18% (n=5).Â For disc diffusion method, resistance index for all isolates were ranged from 0.25 to 0.50. Therefore, proper management in fish farming area and routine monitoring of drug susceptibility patterns overtime is necessary.Â